Evidence-Based Guidelines for Vaginal Hysterectomy of the International Society for Gynecologic Endoscopy (ISGE). Issue 3 (March 2019) - Chrysostomou, Andreas; Djokovic, Dusan; Edridge, William; van Herendael, Bruno J.
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2018;231:262–267) Hysterectomy can be performed abdominally, vaginally, or laparoscopically, with or without robotic assistance. Abdominal hysterectomy (AH) for benign uterine conditions is the most commonly chosen route worldwide.